A Comparison of Intravenous Infliximab Versus Subcutaneous Infliximab on Remission Rates, Safety, Costs, Patient Preferences in Patients With Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis - Alejandro Nieto Dominguez; Abhishek Bhurwal; Hemant Mutneja; Sarah E. Eichinger; Bhanu Pinnam; Daniel Guifarro Rivera; Chun-Wei Pan (Gastro Hep Advances)
Background and Aims: Infliximab, widely used as a mainstay treatment of inflammatory bowel disease (IBD), is traditionally administered intravenously. The subcutaneous (SC) formulation appears to offer a more convenient route of administration. This is a systematic review and meta-analysis comparing the outcomes of intravenous (IV) and SC routes of administration of Infliximab. Methods: All observational studies and randomized controlled trials comparing efficacy, effectiveness, safety, costs, and patient preferences between IV vs SC infliximab in adult human patients with IBD between January 1, 1997, and September 9, 2023, were analyzed. The primary outcome was comparison of the remission rates between SC and IV infliximab in IBD patients. Secondary outcomes were analyzing the different safety profiles and adverse events of IV infliximab vs SC infliximab qualitatively and quantitatively, comparing costs between both groups and evaluating patient preferences among the different studies found on our systematic review. Results: Twenty studies were included in the qualitative synthesis and 9 were included in the quantitative synthesis, with a total of 960 patients. There was no significant difference in clinical remission rates between the IV and SC infliximab groups at 8 weeks, 6 months, and 1 year. Switching to SC infliximab was overall safe. Patient satisfaction was higher in patients using SC infliximab, with additional cost-saving benefits. Conclusion: The systematic review and meta-analysis reveal that SC infliximab could be a safe, cost-effective, well tolerated alternative for achieving disease remission in patients with IBD.